Meningkatkan Kemampuan Membaca Al-Qur’an melalui Metode Tutor Sebaya Siswa Kelas VI SD Negeri 3 Cakranegara - Mahmudah, Siti (TSAQOFAH, 2022)
This study aims: (1) To find out the application of the peer tutoring method in improving the ability to read the Qur'an of Grade VI students of SD Negeri 3 Cakranegara in the odd semester of the 2021/2022 academic year. (2) To find out the results of the application of the peer tutoring method in improving the ability to read Al-Qu'an for grade VI students of SD Negeri 3 Cakranegara in the odd semester of the 2021/2022 academic year. The results showed that peer tutoring model learning had a positive impact in improving student achievement, which was marked by an increase in student learning mastery in each cycle, namely the first cycle (82.14%), in the second cycle to (100%). The peer tutor teaching model can make students feel that they receive attention and the opportunity to express opinions, ideas, ideas and questions. The application of peer tutoring model learning has a positive influence, which can increase student learning motivation.